Sabung Ayam Pada Masyarakat Bali Kuno Abad IX-XII - Saputra K. W., I Wayan Gede (Humanis; Volume 15. No.2. Mei 2016)
Cockfighting is a unique tradition that is closely related to the social life of Balinese Hindu religious community. These activities are very frequent and commonplace found in Balinese life. Related to this activity is still a lot of question, one that perhaps the public is often questioned about when the appearance and how your activities in the past cockfights. That matter is used as a reference in order to uncover and reconstruct how actually means cockfighting activities in the past. The aim of this study was to find out when the emergence of cockfighting, what function cockfight at the time of ancient Bali, and how later developments cockfighting modern times now. Results of this study indicate if new cockfighting activity known by the people of Bali the past in the 10th century, marked by the mention of the term lagan Sawung the inscription Sembiran AI Function cockfight at the time of ancient Bali can be grouped into three, namely, the function of tax object, grace or gift king function, and the function of complementary means of ritual. The development of cockfighting in modern times, seems to evolve into complex forms. Cockfighting in the form of tabuh rah only has changes in the implementation of adaptation bets, while cockfighting in the form tajen undergo dynamic changes both in terms of execution, time, and on spurs and chicken used.
Keywords: Cockfighting, Occurrences, Functions cockfighting, Development.